Design of a Mobile App to Monitor and Control in Real Time Type 2 Diabetes Mellitus in Peru - Ocares-Cunyarachi, Lilian; Andrade-Arenas, Laberiano (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Diabetes in the world is a big problem. In addition, in Peru there are high cases of diabetes mellitus type 2, this happens due to insulin resistance, which causes damage to muscle, liver. In addition to the fact that the fat cells do not generate insulin correctly is because the body needs to generate more insulin so that glucose can enter the cells. Due to the problem that exists, a solution to the problem was sought with the objective of developing the design of a mobile application to monitor in real time, in such a way that it helps patients with diabetes to have a good monitoring plan. The methodology developed in the research is Design Thinking as it fits perfectly to the solution of the problems of society which was successfully developed using the phases of empathizing, defining, ideating, prototyping and finally testing. As a result, the design of the mobile application to monitor and control in real time patients with diabetes mellitus type 2 in Peru was obtained. In addition, obtained data on diabetes in Peru verified by the Ministry of Health, such as the results of registered cases of diabetes in Peru 2022, type of diabetes that develop in Peru on a large scale, type of diabetes in men and women. The complications that arise in the progression of the disease in addition to the cases of records according to sex and period of the year 2020 to 2022. Also, the cases presented diabetes throughout Peru therefore a survey was conducted where professors of the Universidad de Ciencias y Humanidades were conducted to qualify the prototypes for development which returned favorable results for implementation.